Market share analysis of Malaysia's palm oil exports: implications on its competitiveness - Alias, Mohammad; Mohd Arshad, Fatimah; Abdul Rahman, Abdul Aziz (Penerbit Universiti Kebangsaan Malaysia, 1992)
The objective of this article is to analyse the market share of Malaysia's palm oil exports using the constant market share (CMS) approach in order to assess its competitiveness in the world market. Palm oil exports in period 1981·85 were analysed in comparison to the base period 1976·80 quantities. Next, palm oil exports in period 1986-90 were analysed in comparison to period 1981-85, and finally a comparison between period 1981-85 and 1986-90. The results of the CMS analysis show that size of market is the dominant factor in contributing to the country's palm oil export expansion. The competitiveness [actor plays relatively minor role and it is declining over time.